Psychoneuroimmunology in terms of the two main stress axes: Sickness behaviour as trigger for development of mental disorders - Roos, J.L. (Johannes Louw) (University of Pretoria, 2013)
Thesis (DPhil (Psychiatry))--University of Pretoria, 2003.